2009
DOI: 10.1115/1.3068307
|View full text |Cite
|
Sign up to set email alerts
|

Chimney Effect on Natural Convection Cooling of a Transistor Mounted on a Cooling Fin

Abstract: The thermal impedance Zth(jω) has been measured for the junction of a transistor mounted on a cooling fin. The setup was put inside a chimney in order to enhance the natural convection cooling. From the thermal impedance Zth(jω) the influence of the chimney on the reduction in thermal resistance Rth=Zth(jω=0) is clearly visible. A maximum improvement of almost 20% has been observed experimentally. Measuring the thermal impedance as a function of the angular frequency ω provides specific information about the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Measured absolute temperature for the estimated junction temperature (blue curve), heatsink (red curve) and heatsink cover (yellow curve) for 150W power dissipation for cm and 35 cm heatsink It can be seen from Figure 8 that the effect of the heatsink cover is to increase the steady-state junction temperature by only 4 o C, whilst the cover (touch) temperature is it a safe level of 35 o C. It may be expected that the inclusion of a heatsink cover would have a detrimental effect on the junction temperature. However, the modest increase in junction temperature of 4 o C arises to the desirable "chimney effect" [11], which occurs as ambient air is forced upward through the vertically oriented heatsink fins by convection. With the heatsink cover included it was found that for higher values of dissipation, the estimated junction temperature became the limiting factor -maximum 150 o C from section 3.…”
Section: Pec Thermal Experimental Measurementsmentioning
confidence: 99%
“…Measured absolute temperature for the estimated junction temperature (blue curve), heatsink (red curve) and heatsink cover (yellow curve) for 150W power dissipation for cm and 35 cm heatsink It can be seen from Figure 8 that the effect of the heatsink cover is to increase the steady-state junction temperature by only 4 o C, whilst the cover (touch) temperature is it a safe level of 35 o C. It may be expected that the inclusion of a heatsink cover would have a detrimental effect on the junction temperature. However, the modest increase in junction temperature of 4 o C arises to the desirable "chimney effect" [11], which occurs as ambient air is forced upward through the vertically oriented heatsink fins by convection. With the heatsink cover included it was found that for higher values of dissipation, the estimated junction temperature became the limiting factor -maximum 150 o C from section 3.…”
Section: Pec Thermal Experimental Measurementsmentioning
confidence: 99%
“…A vertical space is needed for the vehicles to be transported upwards to the parking tower. This vertical space designed for transportation resembles a chimney, which could facilitate a chimney effect [1][2][3] in case of a fire in the parking tower. The chimney effect can also lead to a rapid spreading of the fire, thus causing heavy losses if rescue is delayed.…”
Section: Introductionmentioning
confidence: 99%
“…This method will be used in this contribution to determine ϕ(τ ) from the experimentally measured T (t). The same technique has also been used intensively for the thermal characterization of semiconductor components and packages [9,10,11,12,13,14,15,16].…”
Section: Experimental Measurementsmentioning
confidence: 99%